Polarity of actin filaments in Characean algae. - Kersey, Y M (1976)
Heavy meromyosin from rabbit muscle combines with oriented Nitella and Chara actin in vitro to form arrowhead structures directed opposite to the cytoplasmic flow in the living plant cell. All filaments and all bundles of filaments in the apically directed stream are similarly oriented; polarity with respect to the axis of the thallus is reversed in the downward stream. The actin filaments are attached to the chloroplasts at the ectoplasm-endoplasm interface, where the motive force for streaming is known to be generated.